2016
DOI: 10.3791/53919
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Atrial Cardiomyocytes from Pluripotent Stem Cells Using the BMP Antagonist Grem2

Abstract: Protocols for generating populations of cardiomyocytes from pluripotent stem cells have been developed, but these generally yield cells of mixed phenotypes. Researchers interested in pursuing studies involving specific myocyte subtypes require a more directed differentiation approach. By treating mouse embryonic stem (ES) cells with Grem2, a secreted BMP antagonist that is necessary for atrial chamber formation in vivo, a large number of cardiac cells with an atrial phenotype can be generated. Use of the engin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Previous studies from other groups have shown that GREM2 is involved in proliferation and differentiation of stem cells. For example, GREM2 promotes the proliferation of myocardial progenitor cells and the differentiation of stem cells into myocytes [ [25] , [26] , [27] ]. Additionally, GREM2 suppresses the osteoblast differentiation of bone marrow-derived mesenchymal stem cells [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies from other groups have shown that GREM2 is involved in proliferation and differentiation of stem cells. For example, GREM2 promotes the proliferation of myocardial progenitor cells and the differentiation of stem cells into myocytes [ [25] , [26] , [27] ]. Additionally, GREM2 suppresses the osteoblast differentiation of bone marrow-derived mesenchymal stem cells [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, GREM2 promotes the proliferation of myocardial progenitor cells and the differentiation of stem cells into myocytes. GREM2 is also known to suppress the differentiation of bone marrow-derived mesenchymal stem cells into osteoblasts [ [25] , [26] , [27] , [28] ]. These findings indicate that GREM2 has a great influence on the proliferation and differentiation of stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…Grem2 is used experimentally to generate cardiomyocytes from mouse embryonic stem cells (ESCs) [18] and BMP-4 inhibits cardiomyocyte differentiation from mouse ESCs [19]. Grem2 was previously shown to induce the differentiation of embryonic stem cells into a cardiomyocyte lineage via the activation of the c-Jun N-terminal kinase pathway [20].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of GREM2 was also found in adult tissues, such as the ovaries, spleen, and brain, and the activity of BMP-responsive promoters was blocked by the binding of GREM2 to BMP-2 or BMP-4 [12], [13]. Recently, GREM2 was reported to inhibit the differentiation of bone marrow-derived mesenchymal stem cells (BMSCs) into osteoblasts as well as the adipogenesis of 3T3-L1 cells [9], [10], [14], [15], [16], [17]. This suggests that GREM2 plays an important role in tissue homeostasis by promoting or inhibiting the differentiation of stem cells.…”
Section: Introductionmentioning
confidence: 99%